Suppression of sui iuris monastery of nuns: Canon 616 §4 (Roman Replies and CLSA Advisory Opinions 2009, 2009)
"A diocesan bishop learned from his vicar for religious that a sui iuris monastery in the diocese had five nuns in their eighties, three of whom were infirm. The vicar reported that during his annual visitations to the monastery, he repeatedly requested that the nuns look to their future and plan for the suppression of the monastery, since the infirm nuns needed provision for assisted living and no vocations were forthcoming for a number of years. However, the nuns refused to take any steps towards the suppression of the monastery and providing for their own retirement needs."